Integrating Environmental Governance and Green Economy: Nepal’s Journey Towards Sustainable Development - Mishra, Anjay Kumar; Prasai, Kul Prasad (Apex Journal of Business and Management, 2025)
Nepal's transition towards a green economy, combined with strengthened environmental governance, embodies a comprehensive approach to sustainable development in the face of climate change and socio-economic vulnerabilities. The 2019 amendment to Nepal’s Environmental Protection Act introduces enhanced legal provisions addressing pollution, climate change mitigation, and environmental compliance. Institutional frameworks are being reinforced to improve enforcement capacities, monitoring, and public participation. Concurrently, Nepal’s green economy initiatives emphasize renewable energy, sustainable agriculture, eco-tourism, and clean transportation, supported by innovative financing mechanisms including green bonds and green finance taxonomy introduced by Nepal Rastra Bank. Collaborative efforts across government, private sector, and grassroots communities, alongside international partnerships such as concessional financing from the Asian Development Bank, are driving inclusive and climate-resilient growth. Despite challenges of financing gaps, infrastructural deficits, and policy fragmentation, Nepal’s integrated approach aims to secure environmental protection while fostering economic prosperity and social equity. This dual focus positions Nepal as a model for sustainable development and green growth, contributing significantly towards achieving Sustainable Development Goals and long-term resilience.